BERAKHIRNYA FRONTIR PERTANIAN: KAJIAN HISTORIS WILAYAH BESUKI, 1870-1970 - Nawiyanto Nawiyanto (LIPI Press, 2012)
This article discusses the agricultural sector of Besuki from an environmental history perspective. The theoretical framework upon which the analysis is built is taken from frontier theories as developed by Turner in the context of American historical experience and Butcher in the context of Southeast Asia. Drawing upon primary and secondary historical source materials, the article argues that the development of the agricultural frontier of Besuki resulted from a combination factors of demography, echnology and overseas market as the driving forces. The inflows of migrant made it possible to exploit the widely available and uncultivated lands for developing commercial crops induced demands from the international markets, and facilitated by the improved technology. The agricultural sector of Besuki translated human agency as an environmental change mover. Human-made landscape grew rapidly and a variety of crops developed from 1870. However, in the 1950s the agricultural frontier of Besuki was closed, as indicated by the decreasing percapita land ownership, the escalating conflicts over lands, and the outgoing migration. This development was also inseparable from the growing environmental consciousness demanding the stoppage of the uncontrolled forest conversion which was also environmentally dangerous for running agricultural activities.